New Developments in Physical Education and Sport - Granero-Gallegos, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Continuous professional development is of great importance if one is to develop quality professional work. This book contains some of the latest research advances related to the field of Physical Education and Sports. In today's globalized world, continuous and permanent education is necessary and essential to complement the initial training and previous experience. In this book, you can find a wide range of works focused on innovative teaching methodologies and psychological variables to take into account to improve classes and training. These studies on the most forward-looking technological advances in physical activity and sports are useful for those who seek to be up-to-date on this type of research. In addition, these studies will be useful to consult regarding current lifestyle, the creation of healthy habits, the promotion of physical activity in one's free time, and the importance of leading an active life.